IMPROVING NEW MEDIA-BASED LEARNING MEDIA DESIGN SKILLS FOR ISLAMIC RELIGIOUS EDUCATION TEACHERS IN RASAU JAYA REGENCY - Sukino, Sukino; Sahri, Sahri; Muhammad, Rijjal Habib; Juharoh, Juharoh; Soleha, Wildatus (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to improve the skills of Islamic Religious Education (PAI) teachers in Rasau Jaya District in designing new media-based learning media. This program is motivated by the rapid development of digital technology and the low utilization of new media by PAI teachers. Method: The research method used is the Community-Based Research (CBR) Method in its implementation using training, mentoring, and evaluation. The target of PAI teacher service is 35 teachers from the Education Office and madrasahs in Rasau Jaya District. The implementation of activities is carried out in stages, starting from identifying teacher needs, training in new media-based media design, to mentoring in making learning media. Result: The results of this research show that there is a significant increase in the understanding of digital technology, which initially had an average score of 50.05 after participating in the training, increasing to 90. In terms of skills in making learning media based on the Canva Application, it has been proven to produce good power point products in terms of design, content and visual appearance according to the informant. The average teacher power point result was 80.00, the average learning video making result was 75.00 and the average learning game making result was 76.00. This training was very effective in improving teachers' understanding and skills in using new media for learning. This effectiveness can be seen from the significant increase in pre-test to post-test scores, participant enthusiasm, and satisfactory technology-based learning product results. The uniqueness of the research is the existence of a more specific picture of the challenges and solutions based on local context in the application of modern learning media. Conclusion: As well as showing the importance of collaboration between teachers, academics, and the education community in developing teacher professional capacity holistically.